3D-Printed Temporary Wing Bride as a Temporary Restoration in the Posterior - Richard Mosch; Maurice Hatzky; Patricia Hatzky; Constantin von See (Hindawi Limited, 2024)
The fear of a missing tooth often leads to postponing the visit at the dentist. While extraction itself is a major stressful experience for the patient, the presence of visible gaps or missing teeth inside or outside the aesthetic zone is a deal breaker for a lot of patients. Bridging the time spent until inserting any final restoration with a provisional enables the patients to still take part in everyday life. This case report shows a new approach for a fixed dental provisional in the anterior region using a printed wing bridge approach to replace an extracted tooth. The provisional was prefabricated, and extraction and integration of the provisional could be placed in a single visit. The chosen approach shows the integrability of 3D printing in everyday practice providing immediate economical and aesthetic treatment.